Energetic Ions Downtail of the Reconnection Site. Issue 1 (17th January 2022) - Birn, Joachim; Hesse, Michael; Runov, Andrei; Turner, Drew L.; Cohen, Ian; Slavin, James A.
Abstract: Using combined MHD/test particle simulations, we explore characteristics of ion (proton) acceleration tailward of a near‐Earth reconnection site. We present spatial distributions and explore acceleration mechanisms and sources of accelerated ions. Acceleration is due primarily due simple crossings of the enhanced electric field near the x‐line or in the departing plasmoid. The energetic particle distributions show the expected energy dispersed tailward streaming at the plasma sheet boundary, while equatorial distributions are more complicated, resulting from different acceleration sites within the moving plasmoid. Sources are mostly inside the central plasma sheet dawnward of the plasmoid. Key Points: Energetic ion fluxes form tailward beams surrounding the plasmoid but multiple separate branches near the equatorial plane Boundary beams are primarily accelerated near x ‐line, equatorial acceleration occurs anywhere across tailward propagating plasmoid Origins of accelerated ions are primarily in the downward central plasma sheet